Evaluation of Structural Behavior of Hysteretic Steel Dampers under Cyclic Loading - Sang-Woo Kim; Kil-Hee Kim (Applied Sciences, 2020)
This study proposes a relatively simple steel damper with high energy dissipation capacity. Three types of steel dampers were evaluated for structural performance. The first damper with U-shape had two vertical members and a semicircular connecting member for energy dissipation. The second damper with an angled U-shape replaced the connecting member with a horizontal steel member. The last damper with D-shape had a horizontal member added to the U-shaped damper. All the dampers were designed with steel plates on both sides that transmitted external shear force to the energy-dissipating members. To evaluate the structural performance of the dampers, an in-plane cyclic shear force was applied to the specimens. The D-shaped damper showed ductile behavior with excellent energy dissipation capacity after yielding without decreasing in strength during cyclic load. In other words, the D-shaped specimen showed excellent performance, with about 3.5 times the strength of the U-shaped specimen and about 3.8 times the energy dissipation capacity due to the additional horizontal member. Furthermore, the efficient energy dissipation of the proposed D-shaped steel damper was confirmed from the finite element (FE) analytical and experimental results.